PENGARUH FREKUENSI PERDAGANGAN SAHAM, NILAI PERUSAHAAN DAN TINGKAT KINERJA KEUANGAN TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN AGRIBISNIS YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Rifani Akbar Sulbahri; Firmansyah Arifin; Padriyansyah . (JURNAL KOMPETITIF, 2018)
The objective of this study was to find out and analyze the impact of financial performance against Stock of Return on Index Agri companies in Indonesia Stock Exchange period 2015-2017. The data were analyzed by using logistic regression analysis model. There were five variables in this research. Dependen variabel was Stock of Return is proxied. Independen variabel in this research was Frequency of trading ,Price Book Value (PBV) as a proxy of the stock value, Return on Assets  (ROA) as a proxy of profitability, Return on Equity  (ROE) as a proxy of profitability and Debt to Equity Ratio (DER) as a proxy capital stuctureThese results of logistic regression showed that the variabels Frequency of trading ,Price Book Value (PBV) as a proxy of the stock value, Return on Assets  (ROA) as a proxy of profitability, Return on Equity  (ROE) as a proxy of profitability and Debt to Equity Ratio (DER) as a proxy capital structure variable has no effect on stock of return on Index Agri companies in Indonesia Stock Exchange 2015-2017. This research give due consideration to the company's management to consider the financial governance of the company to generate earnings and stock of return. For investors can raise the level of profitability as the main indicator in determining investment decisions to maximize income from dividends on shares held and capital again. Keywords: Stock of Return, Frequency of Trading, Price Book Value,,Return on Assets, Return on Equity, Debt to Equity, Logistic Regression